Impact of Self-Help Groups, Capacity Building Measures and Perceived Tension on Women Empowerment- An Empirical Study - P.S, Varsha; K, Gayathri Reddy; L.N, Sudheendra Rao; Kumar , Amit (Asian Journal of Empirical Research, 2019)
The current research seeks empirical insights into the women empowerment (WE) by focusing on the role of the self-help groups (SHG), capacity building (CB) measures and perceived individual tension (T). By applying multiple regression analysis on 351 survey responses in India, our findings suggest that WE emerges from two distinct attributes of the SHG members: surface-level (e.g., age, marital status, no. of children, income, whether spouse working, any other assistance) and deep-level (e.g., years of SHG membership, amount of loan availed, purpose of loan, educational level). Moreover, WE is a combination of five broad dimensions such as economic, political, social, legal and psychological empowerment. Further, a set of capacity building measures (i.e., training on governance, technology-driven livelihood support, promoting networking, social justice and harmony) helps to empower women. The study also explores four different categories of perceived individual tension (i.e., economic, social, legal, and technology-oriented learning) and their effects on WE. Finally, the perceived tension moderates the relationship between deep-level SHG attributes and WE.